Utilization of Shrimp Shell Meal Containing Chitosan as a Source of Prebiotic in Preweaned Crossbred Piglets - Kumar, M. Yugandhar; Ramana, J.V.; Ravi, A.; Suresh, J.; Sivakumar, A.V.N. (Indian Journal of Animal Nutrition, 2018)
The effect of inclusion of antibiotic or chitosan from shrimp shell meal (SSM) as prebiotic in the diet was evaluated using 240 pre-weaned piglets (10 d of age). The standard creep ration (T1) was supplemented with chlorotetracyclin (T2) while SSM was included at 0.5 (T3), 1.0 (T4) and 1.5% (T5) level as a source of chitosan. Each treatment consisted of 6 pens with 8 piglets per pen. The animals were provided with feed and water ad lib. during the experiment for 42 days. Higher (P<0.01) body weight gain and superior (P<0.01) feed/ kg gain was observed in treatments T2 to T5 than in T1. The total creep feed intake of piglets was similar in all the treatments. The villus height of duodenum, jejunum and ileum as well as the ratio of villi height to crypt depth increased (P<0.01) quadratically due to supplementation with increasing levels of SSM. The gut pathogen load (E. coli and Salmonella) was also reduced in all the groups. The results indicated that chitosan contained in SSM was effective as a prebiotic to improve growth in pre-weaned piglets.